Performance management by culture in the NLRB's division of judges and the German labor courts of Appeal - Martin Schneider (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2002)
Professional judges receive a fixed salary and are largely exempt from disciplinary sanctions. How can performance still be secured? Judges share a culture consisting of work-related norms and values, derive status from their standing within the professional community, and are susceptible to peer review. Hence, performance can be managed by maintaining and directing culture. This is illustrated in a case study on the administrative law judges at the U.S. National Labor Relations Board and the judges at the German labor courts of appeal. In both judiciaries, administrative tasks such as personnel selection are delegated to peers, candidates with known norms and values are recruited, and a quantitative benchmarking appeals to judges' norms and values. In sum, performance management relies in each case on professional culture although the two communities of judges belong to differing national cultures and are governed by differing administrative rules.
Keywords: J45; M12; K49; 330; performance management; organizational culture; labor judiciaries